Training On Making Perfomed Herbs Jahe Instant In The Village Of Banda Buek The City Of Padang - Rika Sepriani (Jurnal Humanities Pengabdian Kepada Masyarakat, 2021)
Medicinal herb is known as "herbal medicine". Based on the observations that have been made, the community in each house in the village of Bnadar Buat has plants that can be categorized as medicinal plants. They know what plants are used as medicine but the utilization is not optimal because of the lack of knowledge of the public on how to use medicinal plants as traditional medicine appropriately and correctly and how to process them into high economic value products, one of which is the herbal preparation of instant ginger powder. To overcome this, it is necessary to provide information and knowledge as well as training on the preparation of instant ginger powder herbs of high economic value. Before carrying out the activities of the PKM team conducted a socialization stage by inviting PKK mothers in bandar Buat village. This devotional activity uses a way of giving material through lectures, then continued with direct practice by pkk mothers. All participants were involved and each group did its own division of work within the group. From this activity resulted in increased knowledge of PKK mothers about medicinal plants as well as the instigated preparation of instant ginger powder herbs of economic value.